Brazilian Plants: An Unexplored Source of Endophytes as Producers of Active Metabolites - Savi, Daiani Cristina; Aluizio, Rodrigo; Glienke, Chirlei (Planta Medica, 2019)
Brazil has an extraordinary biodiversity, and for many years, has been classified as the first of 17 countries with a mega diversity, with 22% of the total plants in the world (more than 55 000 species). Considering that some endophytes are host-specific, the incomparable plant diversity found in Brazil encompasses an immeasurable variety of habitats and may represent a repository of unexplored species. As a result of the endophyte-host interaction, plant-associated microorganisms have an enormous biosynthetic potential to produce compounds with novelties in structure and bioactivity. Numerous studies have been published over the years describing the endophytic species isolated in Brazil. Identification of these species is generally performed via DNA sequencing. However, many of the genera to which the described taxa belong were reviewed phylogenetically and many species were reclassified. Thus, there is a gap in the real biodiversity of endophytes isolated in Brazil in the last decade. In this scenario, the present study reviewed the biodiversity of endophytes isolated from plants found in different Brazilian biomes from 2012 to 2017, including the following topics: (i) species diversity, (ii) species identification challenges, (iii) biotechnological aspects, and (iv) identified metabolites. Endophytes of 54 species of plants were studied from 2012 to 2017, resulting in the identification of 300 genera, with Diaporthe and Bacillus being the most frequent fungal and bacterial genera, respectively.
Keywords: Brazilian biodiversity; medicinal plants; endophytes; secondary metabolites